Agriculture role in social-economic resilience to majo economic crises in Romania - Monica Mihaela Tudor (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The objective of this analysis is to investigate the capacity of agriculture to actively contribute to reducing vulnerabilities and the degree of exposure of Romania's economy to shocks caused by major economic crises. The role of agriculture, as economic and social resilience factor, is analyzed from the perspective of primary sector contribution to the attenuation of shock and to the recovery following the economic-financial crisis that started in 2008. The primary sector contribution to counterbalancing the negative effects on GDP and labour employment generated by the recent economic crisis, by increasing the turnover in agriculture and reasserting the role of occupational outlet, in the conditions of shortage on the labour market, represent a few arguments in favour of the assertion that Romania's agriculture is a system with relatively high resilience to shocks and at the same time a supplier of economic and social resilience for the entire economy.
Keywords: O11; Q1; E24; 330; resilience; agriculture; economic crisis; Romania